Evaluation of transtrochanteric rotational osteotomy for avascular necrosis of hip: a case series - Ragase, Ashish Kumar; Dubey, Anuranjan (International Journal of Research in Orthopaedics, 2021)
Osteonecrosis, also referred to as avascular necrosis (AVN), aseptic necrosis and ischemic necrosis, is not a specific disease but rather a condition in which a circumscribed area of bone becomes necrotic as a result of a loss of its blood supply. The femoral head is the site most often affected and its frequent cause is a displaced fracture through the femoral neck. This is a case-series study that has been done on 9 patients (10 hips) with clinical and radiological evidence of osteonecrosis of head of femur. After treatment patients were followed clinically and radiographically at 1 to 3 months intervals during first year after the operation and at 3 to 6 months intervals thereafter. Out of 9 study subjects, 7 (77.7%) were male and 2 (22.2%) were female. Mean age was 40±7.5. Among 7 (70%) hips, canulated cancellous screws were used and dynamic hip screw were used in 3 (30%) hips. Majority of the cases, 4 (40%) had more than 2 mm of progressive collapse of transported intact area in their latest follow up. Transtrochanteric rotational osteotomy procedure is valuable and needs to be tried by new genre of orthopedician as it helps in clinical improvement of patient and might also delay the necessity for total hip arthroplasty.